2009
DOI: 10.1142/s1793604709000600
|View full text |Cite
|
Sign up to set email alerts
|

SHAPE MEMORY EFFECT AND CYCLIC DEFORMATION BEHAVIOR OF TiNbN ALLOYS

Abstract: The effect of 1 at.% N addition on the shape memory effect of Ti-Nb alloys was investigated. The shape memory effect and superelasticity were observed in Ti-(18-20)Nb-1.0N and Ti-(21-25)Nb-1.0N alloys, respectively. The Ti-23Nb-1.0N alloy exhibits the best superelastic properties with almost perfect recovery and small stress hysteresis among N added ternary alloys. The effect of cyclic deformation on the stability of superelasticity was investigated for the Ti-23Nb-1.0N alloy by loading and unloading cyclic te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 13 publications
0
23
0
2
Order By: Relevance
“…For Ti-xNb-1O alloys, superelasticity is observed when x is 22 at%, 48) implying that the addition of 1 at% O to Ti-Nb alloys decreases M s by about 160200 K because the effect of 1 at% O in decreasing the martensitic transformation temperature is equivalent to that of 45 at%Nb. N shows a similar effect on the martensitic transformation temperature; the addition of 1 at% N to Ti-Nb 49) and Ti-Nb-4Zr-2Ta 90) alloys decreases M s by about 200 K. However, the martensitic transformation temperature decreases by 75 K with 1 at% increase of N content for the Ti-18Zr-13Nb alloy. 91) It is suggested that this weaker effect of N on the martensitic transformation temperature in the alloy with relatively a higher content of Zr is due to its larger lattice parameter.…”
Section: Effect Of Interstitial Alloying Elementsmentioning
confidence: 82%
See 1 more Smart Citation
“…For Ti-xNb-1O alloys, superelasticity is observed when x is 22 at%, 48) implying that the addition of 1 at% O to Ti-Nb alloys decreases M s by about 160200 K because the effect of 1 at% O in decreasing the martensitic transformation temperature is equivalent to that of 45 at%Nb. N shows a similar effect on the martensitic transformation temperature; the addition of 1 at% N to Ti-Nb 49) and Ti-Nb-4Zr-2Ta 90) alloys decreases M s by about 200 K. However, the martensitic transformation temperature decreases by 75 K with 1 at% increase of N content for the Ti-18Zr-13Nb alloy. 91) It is suggested that this weaker effect of N on the martensitic transformation temperature in the alloy with relatively a higher content of Zr is due to its larger lattice parameter.…”
Section: Effect Of Interstitial Alloying Elementsmentioning
confidence: 82%
“…2533) Particularly, there has been tremendous progress in developing Ti-Nb base shape memory alloys in the past decade and many Ti-Nb base alloys have been developed, e.g. Ti-Nb-Sn, 26,34) Ti-NbAl, 31,32,35) Ti-Nb-Ta, 36,37) Ti-Nb-Zr, 3844) Ti-Nb-Mo, 45,46) TiNb-Pd, 47) Ti-Nb-O, 48) Ti-Nb-N, 49,50) Ti-Nb-Pt, 51) Ti-Nb-TaZr, 5254) Ti-Nb-Zr-Sn, 5557) Ti-Nb-Mo-Sn, 5860) Ti-Zr-NbSn, 61) Ti-Nb-Zr-Al 62) and Ti-Nb-Zr-Mo-Sn. 63) This paper aims to provide an overview of the recent works on Ti-Nb base shape memory alloys.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, Ti-Nb-base alloys have been extensively studied as promising candidates for Ni-free biomedical shape memory alloys, and many alloys have been reported to exhibit superelasticity at room temperature [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. For the binary Ti-Nb alloys, superelastic recovery was observed when the Nb content is 26-27 at.% [4]; however, the recovery strain was as small as about 3 % even including elastic strain, which is quite smaller than those of practical Ti-Ni superelastic alloys [15].…”
Section: Introductionmentioning
confidence: 99%
“…Addition of ternary or quaternary elements, such as Zr, Sn or Al, can also improve superelasticity [2,[13][14][15][16]. Particularly, addition of interstitial elements (O or N) allows a strong improvement of both superelastic properties and mechanical strength in binary Ti-Nb based alloys [2,7,17,18] or in more complex Ti-Nb based compositions [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%